Congestion bottleneck avoid routing in wireless sensor networks - Sanu Thomas; Thomaskutty Mathew (Institute of Advanced Engineering and Science, 2019)
A new efficient method for detecting congested bottleneck nodes and avoiding them in the route formation in a wireless sensor network is described. Sensor nodes with a higher degree of congestion are excluded while determining the best routing path from a given source to destination in a multi-hop transmission. In a scenario where different communication paths have different maximum congestion levels, selecting that path which has least maximum congestion, is a challenging task. A modified Bellman-Ford algorithm is proposed to solve this problem efficiently. The proposed technique is very much useful for the optimal route selection for vehicles in metropolitan cities that avoids high traffic density junctions. Once the desired destination is specified, the traffic control system can use this algorithm to provide the least congested routes to the intra-city vehicles.